การประเมินจุดอ่อนด้านซอฟต์แวร์ของระบบเว็บเซอร์วิสโดยจำแนกความรุนแรงของความเสียหาย - กิตติศักดิ์ นิทาน (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research assesses software vulnerability of web services products based on Common Vulnerability and Exposure (CVE) and classifies the damage of each vulnerability into confidentiality, integrity, and availability. The impact of each vulnerability type of web services products have been classified to development tools and runtime service tools. We use scores of impacts to compute severity of damage on web services products and compare each type of damage.